Antifungal activity of lactic acid bacteria and their application for Fusarium mycotoxin reduction in malting wheat grains. (March 2018) - Juodeikiene, Grazina; Bartkiene, Elena; Cernauskas, Darius; Cizeikiene, Dalia; Zadeike, Daiva; Lele, Vita; Bartkevics, Vadims
Abstract: This study mainly focuses on finding a strategy for reduction of Fusarium mycotoxin in malting wheat grains, predominantly used in the production of beverages and certain baked goods. The effect of treatment with lactic acid bacteria (LAB) on deoxynivalenol (DON), zearalenone (ZEN), T-2 and HT-2 toxins contained in malting wheat grains was studied. Additionally, the impact of bio-treatment with bio-products based on cheese whey permeate previously fermented with LAB on microbial contamination and germination capacity of grains was studied. Treatment with Lactobacillus sakei KTU05-6, Pediococcus acidilactici KTU05-7, and Pediococcus pentosaceus KTU05-8, KTU05-09, and KTU05-10 strains resulted in reduction of ZEN, DON, T-2 and HT-2 toxin concentrations in malting grains by 23, 34, 58 and 73% respectively. Moreover, the test of LAB strains revealed a broad spectrum of antimicrobial activity against fungi, especially Fusarium culmorum and Fusarium poae . Treatment of contaminated wheat grains with permeate previously fermented with P. acidilactici KTU05-7 and P. pentosaceus KTU05-10 strains resulted in increased germination of wheat grains by 9.5 and 7.9% respectively comparing with grains that were not pre-treated. Highlights: The treatment of malting grains with LAB metabolites caused reduction of mycotoxins. Pediococcus pentosaceus strains caused significant reduction of mycotoxins. LAB showed antifungal activity against fungi and yeast occurred on malting grains. The treatment of malting grains with fermented permeate showed antifungal effect. The reduction of moulding during grains germination was influenced by LAB.